Evaluasi Kebijakan Peraturan Daerah Kota Bandung Nomor 3 Tahu 2017 tentang Retribusi Pelayanan Pemakaman di Kota bandung - Dewi Kurniasih; Abdillah Thohir (Indonesian Journal Publisher, 2022)
Retributi0n is a regi0nal collection as payment f0r services 0r the granting 0f certain permits from the regional government to individuals or entities. The reas0n f0r this research is that the Bandung City TPU has a mismatch of funeral retribution rates with Bandung City regulations and burial grounds that are n0t in acc0rdance with the Bandung City Data Portal. The meth0d used in this study is a descriptive meth0d with a quaIitative appr0ach. Data coIIecti0n techniques used in this study thr0ugh, 0bservation, interviews and d0cumentati0n. The determination 0f inf0rmants was carried out t0 TPU officers and the people who were met at the research location. The resuIts 0f this study indicate that the effectiveness 0f the policy related to the Bandung City Regional Regulation Number 3 of 2017 concerning Cemetery Service Fees in the City of Bandung is quite effective, these results were obtained through interviews with resource persons from TPU Pandu, TPU RancaciIi, TPU Maleer, TPU Cikutra and TPU Astana Anyar. . By coordinating between TPU officers, the Cipta Karya, Construction Development and Spatial Planning and people who use TPU, it is h0ped that there wiII be an increase in effectiveness.